2020
DOI: 10.1038/s41586-020-2072-8
|View full text |Cite
|
Sign up to set email alerts
|

A mycobacterial ABC transporter mediates the uptake of hydrophilic compounds

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 41 publications
6
92
0
1
Order By: Relevance
“…Despite the name, it has generally not been experimentally demonstrated that exporters have a unique transport directionality, or how this directionality is maintained. An informative example is provided by the recent studies of mycobacterial ABC transporters with exporter folds that mediate the uptake of various water-soluble compounds ( 6 , 7 ). The structural characterization of ABC exporters in distinct conformational states has been achieved primarily by controlling the nucleotide state, often in combination with the ATPase deficient “E-to-Q” mutant in the Walker-B motif ( 8 ).…”
mentioning
confidence: 99%
“…Despite the name, it has generally not been experimentally demonstrated that exporters have a unique transport directionality, or how this directionality is maintained. An informative example is provided by the recent studies of mycobacterial ABC transporters with exporter folds that mediate the uptake of various water-soluble compounds ( 6 , 7 ). The structural characterization of ABC exporters in distinct conformational states has been achieved primarily by controlling the nucleotide state, often in combination with the ATPase deficient “E-to-Q” mutant in the Walker-B motif ( 8 ).…”
mentioning
confidence: 99%
“…We also observed overexpression of histidine metabolism in DKD; its product histamine might be involved in mediating the inflammatory response [ 51 ]. ABC transporters mediate the transport of hydrophilic compounds and promote the growth of various bacteria, such as Mycobacterium tuberculosis [ 52 ]. The PTS is involved in the phosphorylation of sugars [ 53 ], and the interconversion of pentose and glucoronate provides substrates for the synthesis of nucleic acids and maintains the reducing state of glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore appears that cobamide remodeling mechanisms have independently evolved multiple times. Together with the multiple pathways that exist for cobamide biosynthesis, transport, and precursor salvaging (31,33,35,(93)(94)(95)(96)(97)(98)(99), the addition of CbiR to the growing list of enzymes involved in cobamide metabolism highlights the importance of cobamide physiology in the evolution of bacteria.…”
Section: Discussionmentioning
confidence: 99%